“Crown for Women on Empowerment Program”: Studies of Important Position of Women in Poverty Alleviation Program in Banyumas - Indiahono, Dwiyanto (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTWomen in rural areas with low education and experience are feared to be problems on poverty alleviation programs. Research forwomen position in poverty alleviation programs based onPNPM-Mandiri Perdesaan (rural empowerment) thus becomes strategic. This research seeks to find out, how the role of women in poverty programs?; and how important is the position of women in poverty alleviation programs?. Qualitative research has been carried out by conducting in-depth interviews and focus group discussion (FGD) to the members of women’s groups, activists, actors and managers of PNPM-Mandiri Perdesaan in Banyumas Regency. Triangulation and interactive data analysis has been carried out strictly and carefully. The results showed that social capital of women groups has proven to be a major force to support the success of the poverty alleviation program.This makes the position of women is very important in this program.The important position is characterized by a strong social capital, unity of purpose, solidarity of groups, an excellent adaptation to change, and internalization of the program so that the objectives can be achieved.This study believes that the inclusion of women in poverty alleviation programs in rural areas is one of the best ways.Keywords: development, empowerment, poverty, social capital, and women.ABSTRAKPerempuan di daerah pedesaan dengan pendidikan dan pengalaman yang rendah dikhawatirkan menjadi masalah pada program pengentasan kemiskinan. Penelitian tentang posisi penting perempuan dalam program pengentasan kemiskinan berbasis PNPM-Mandiri Perdesaan (pemberdayaan pedesaan) menjadi strategis. Penelitian ini mengungkapkan, bagaimanakah peran perempuan dalam program pengembangan pengentasan kemiskinan?; dan seberapa pentingkah posisi perempuan dalam program pengentasan kemiskinan?. Penelitian kualitatif telah dilakukan dengan melakukan wawancara mendalam dan focus group discussion (FGD) dengan anggota perempuan kelompok, aktivis, aktor dan manajer kegiatan PNPM-Mandiri Perdesaan di Kabupaten Banyumas. Triangulasi dan analisis data interaktif telah dilakukan secara ketat dan hati-hati. Hasil penelitian menunjukkan bahwa modal sosial kelompok perempuan telah terbukti menjadi kekuatan utama yang mendukung keberhasilan program pengentasan kemiskinan. Hal ini membuat posisi perempuan sangat penting dalam program ini. Posisi penting ini ditandai dengan modal yang kuat sosial, kesatuan tujuan, solidaritas kelompok, adaptasi yang sangat baik untuk perubahan, serta internalisasi program sehingga tujuan dapat dicapai. Penelitian ini percaya bahwa melibatkan perempuan pedesaan dalam program pengentasan kemiskinan di akar rumput pedesaan adalah salah satu cara terbaik.Kata kunci: pembangunan, pemberdayaan, kemiskinan, modal sosial, dan perempuan.